2020
DOI: 10.1080/01587919.2020.1821602
|View full text |Cite
|
Sign up to set email alerts
|

Role of gender and social context in readiness for e-learning in Saudi high schools

Abstract: There is limited evidence of the effects of culture and context on student readiness for e-learning, and how these might interact with gender. This study addresses this gap by studying the effect of culture and context on the readiness of high school students to use e-learning in a unique setting: an education system in which male and female students are educated separately. A mixed methods research approach was adopted because of our emphasis on the subjective aspect of the concept of readiness. Findings demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Moreover, perceived usage experience, the intention to learn, and the benefit of technology-based learning were found to be slightly lower among males than females (Ramírez-Correa et al 2015 ). Similarly, a mixed-method study finding in Saudi Arabia, Mutambik et al suggested gender divide investigations of e-learning readiness in deferent cultural setting (Mutambik et al 2020 ). In addition, Bangladesh Nursing and Midwifery Council (BNMC) allows 90% of its seat for female students during admission.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, perceived usage experience, the intention to learn, and the benefit of technology-based learning were found to be slightly lower among males than females (Ramírez-Correa et al 2015 ). Similarly, a mixed-method study finding in Saudi Arabia, Mutambik et al suggested gender divide investigations of e-learning readiness in deferent cultural setting (Mutambik et al 2020 ). In addition, Bangladesh Nursing and Midwifery Council (BNMC) allows 90% of its seat for female students during admission.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of mathematics, there are no studies that analyze the influence or relationship between gender or age and the e-learning method. However, there are studies that relate the gender and age of students to the application of e-learning (Mutambik, Lee & Almuqrin, 2020). In relation to gender, there are results that show that the existing reduction of the gender gap is occurring faster in more developed cities (Yawson, 2021).…”
Section: Research Articlementioning
confidence: 99%
“…In [15][16][17][18], authors emphasized that e-learning is one of the comfortable means of education for learners as it provides educational content in any place and time and this is not possible to fully achieve it in the traditional study style in the classroom. In [19][20][21], they emphasized that the learner can bypass the state of boredom in e-learning and focus on important things, unlike traditional education in the classroom where everyone is forced to focus at the same time.…”
Section: Previous Studiesmentioning
confidence: 99%